P3.065 Partner-Concurrency Associated with HSV-2 Infection in Young South Africans. (13th July 2013) - Kenyon, C; Colebunders, R; Buve, A; Hens, N
Abstract : Objectives: While much is known about the individual level risk factors for HSV-2 infection, little is known about why only some populations develop generalised HSV-2 epidemics. This study aims to assess the extent to which partner-concurrency (a factor which operates at both the partnership- and network-level) may be responsible. Methods: We utilised multivariate logistic regression to analyse the relationship between HSV-2 seropositivity and potential risk factors in data from a representative cross-sectional survey of 14–24 year olds from a township in South Africa. Results: The overall prevalence of HSV-2 was 53.3% among women and 17% among men. For men four factors remained significantly associated with HSV-2 infection in the multivariate regression analysis; total number of sex acts, being a migrant labourer, Zulu ethnicity and being HIV positive. For women eight factors were associated with HSV-2 infection; increasing age, partner concurrency (having a partner who had other partners), an older partner, total number of sex acts, using hormonal contraception, Xhosa ethnicity, syphilis seropositivity and being HIV positive. Conclusion: Partner-concurrency is associated with increased HSV-2 seropositivity in women.